A feasibility study on an interlocking storage container and flotation device (Noah's Chest) - Layug, Patricia; Lien, Ace Anton; Ramos, Edissy Claudine; Solitario, Adrian James
In the last ten years, storms and floods had contributed an alarming cumulative of 45.98% and 37.93%, respectively,in the natural disaster frequency in the country from 2005 to 2014. Annually,there are around 3,000 drowning cases in the country. A large percentage of these deaths are due to floods. In order to decrease the number of drowning, Department of Health (DOH) recommends utilization of flotation devices. An opportunity was seen by the group that there is a need for both a reliable flotation device and a waterproof storage container that can hold supplies.Currently, the market does not offer this item. This would make a great opportunity for a business venture. Noah's Chest is an interlocking storage container capable of withstanding external and physical flood pressures. As a storage container, the main function of Noah's Chest is to secure the user's possessions. The chest can be also used as a flotation device during extreme flooding. It comes in three parts: the lid, base, and the 'key'. This container will be made of plastic. Noah's Chest will mainly be sold to intermediate organizations be it government institutions like Local Government Units and National Government Organizations which seek to distribute Noah's Chest to low-income bracket families in flood prone areas in the National Capital Region. More than 90% of the population in NCR is considered as low-income families. The main manufacturing plant of Noah's Chest will be located in Valenzuela City since it has lower costs and appropriate lot sizes. This is also near to the company's suppliers. All process will be covered by the company except the distribution to the target market. It will be done by a third party logistics company. The initial investment cost for Noah's Chest will be PhP 4,419,612. All of the cost will be capitalized by the incorporators. The company is expected to be profitable in the second year of business. From the financial tests and ratios done, it can be seen that the company becomes more profitable as its profitability ratios increase as it progresses the 5-year period of the study. The project is considered to be feasible as it has a positive net-present value. Having total cost and benefit values of 30 million PHP and 1.5 billion PHP, respectively, the project has a cost-benefit ratio of 49.0357. This high value implies the social profitability of Noah's Chest. The benefits that this project will bring about outweigh the associated costs. Furthermore, the project is deemed socially and economically profitable, thus worthwhile to push through.